Parameters of intensity distribution in the Izmit and Dazce (Turkey) earthquakes - LEKKAS, E. L. (Bulletin of the Geological Society of Greece, 2001)
On 17th August and 12th November 1999 the wider area of Izmit, Adapazari, Dózce and Bolu (Turkey) was hit by two seismic shocks with magnitude Mw = 7.4 and Mw = 7.1, respectively. The earthquakes produced surface ruptures over a distance of at least 150 km, as well as settlement, soil fissures, liquefaction, landslides, tsunamis and subsidence. Damage and intensity evaluation followed the EMS]99, and EMS1998. The maximum intensities approached XII in both earthquakes. Intensity maps show alignment parallel to the strike of the seismic faults, with local variations due to geometry and kinematics of certain tectonic structures. Intensities were considerably amplified locally by concomitant geodynamic phenomena